Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1155/2015/787451
|View full text |Cite
|
Sign up to set email alerts
|

The “Gender Factor” in Wearing‐Off among Patients with Parkinson’s Disease: A Post Hoc Analysis of DEEP Study

Abstract: Background. The early detection of wearing-off in Parkinson disease (DEEP) observational study demonstrated that women with Parkinson's disease (PD) carry an increased risk (80.1%) for wearing-off (WO). This post hoc analysis of DEEP study evaluates gender differences on WO and associated phenomena. Methods. Patients on dopaminergic treatment for ≥1 year were included in this multicenter observational cross-sectional study. In a single visit, WO was diagnosed based on neurologist assessment as well as the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
46
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 30 publications
7
46
0
2
Order By: Relevance
“…Contrary to some studies but consistent with others, gender was not an independent predictor of either dyskinesia or MF. Caffeine intake, which other studies have shown to be protective, had no effect in our study.…”
Section: Discussionsupporting
confidence: 74%
“…Contrary to some studies but consistent with others, gender was not an independent predictor of either dyskinesia or MF. Caffeine intake, which other studies have shown to be protective, had no effect in our study.…”
Section: Discussionsupporting
confidence: 74%
“…At symptom onset, male PD patients are more likely to present with axial impairment when compared to female patients . Conversely, as the disease progresses, female PD patients seem to be at higher risk to develop treatment‐related motor complications . Indeed, it has been shown that prevalence of wearing‐off is higher in female than in male PD patients .…”
mentioning
confidence: 99%
“…2,3 Conversely, as the disease progresses, female PD patients seem to be at higher risk to develop treatment-related motor complications. 4,5 Indeed, it has been shown that prevalence of wearing-off is higher in female than in male PD patients. 5 Similarly, the sex difference has been shown to be the most relevant independent predictor of levodopa-induced dyskinesia, irrespective of body weight 5 and treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The disease is more common in men than in woman by an approximate ratio of 1.5-2:1 [18,19]. In addition to prevalence, several other PD-coupled parameters differ between men and women, including onset of symptoms, types of motor and non-motor symptoms, medication use, the effect size of PD risk factors, levodopa bioavailability, neuropsychiatric, and cognitive changes, development of hallucinations, caregiver utilization and reliance, and the quality of life [20,21]. In women, the age of PD onset has shown a positive correlation with fertility.…”
mentioning
confidence: 99%